Synthesis and characterization of some new Indazolone and Carbohydrazide derivatives from azachalcones (Journal of Pharmaceutical Negative Results, 2022)
Pyridine-4-carboxaldehyde can be used for the synthesis 1-aryl-3-(2-pyridyl)-2-propenone(4-azachalcone)(m1-m3) by coupling with acetophenone, 4-methyl acetophenone and 4-amino acetophenone in basic medium. The compounds (m1-m3) converted by Robinson annulation reaction to form the corresponding cyclohexenone derivatives (m4-m6) by coubling with ethyl acetoacetate after mandate reflux. Reaction of cyclohexenone derivatives (m4-m6) with hydrazine hydrate (99%) in presence of some drops glacial acetic acid gives Indazolone derivatives (m7-m8). On the other side, the synthesized cyclohexenone (m4-m6) were treated with hydrazine hydrate (99%) in absolute ethanol to yield carbohydrazide derivatives (m9-m11).The chemical structures of the new compounds (m1-m11) were established on the basis of some physical properties and some spectroscopy methods like, FT-IR, 1HNMR and 13C-NMR spectra. Also, all these reactions followed by thin layer chromatography (TLC) technique.